Past industrial traces of the Jasień River in the tourism space of Łódź - Jędruszkiewicz, Joanna; Moniewski, Piotr (Turyzm/Tourism, 2015)
In the paper the characteristics of one of the most valuable rivers in Łódź, the Jasień, are described. The Jasień is a unique example of a river once working for industry but now existing as untapped tourism potential despite its negative image and even being partly forgotten. The description of the most valuable historical hydro-technical work along the river’s course is given with some useful historical information. In the summary, a suggestion of how the river bank might become a trigger for studying Łódź’s history, as its industrial development was so strongly related to the river network.